PENGUATAN LITERASI BUDAYA DALAM PEMBELAJARAN BAHASA INDONESIA MELALUI MEDIA TEKS NARASI BERMUATAN KEARIFAN LOKAL - Kayati, Afiyah Nur (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2020)
The era of the industrial revolution 4.0 provides many challenges for students. These challenges not only focus on cognitive intelligence, but also intelligence in acting primarily in responding to cultural diversity. Cultural literacy is a basic skill that must be mastered by students that can be integrated into learning in schools. Through cultural literacy, students can increase knowledge and skills in understanding and behaving towards Indonesian culture as a national identity. This study aims to describe the strengthening of cultural literacy in Indonesian language learning through narrative texts that are loaded with local wisdom. This research is a qualitative research with literature study method. The strategy of cultural literacy in Indonesian language learning in schools can be done by providing narrative texts containing local wisdom as teaching media. The narrative text can be in the form of fiction narrative and non-fiction narrative. Culture, customs, and philosophy of life of the people contained in the narrative text containing local wisdom can increase students' knowledge about the culture of the region that they do not know yet. The narrative text of local wisdom contains noble values that can increase students' ability in responding to cultural diversity.